Round - Sidman, Joyce; Yoo, Taeeun (2017)
"Newbery-Honor winning poet Joyce Sidman invites readers to search their worlds for round objects in nature. Illustrated with warm, intimate art by two-time New York Times Best Illustrated artist Taeeun Yoo, this fresh celebration shows why we love this shape best."--
Ages 4-7.
K to grade 3.
Keywords: Shapes -- Juvenile literature; Geometry, Solid -- Juvenile literature